Techno-Economic Analysis as a Driver for Optimisation of Cellobiose Lipid Fermentation and Purification - Oraby, Amira; Rupp, Steffen; Zibek, Susanne (Frontiers in Bioengineering and Biotechnology, 2022)
Cellobiose lipids (CL) are glycolipids synthesized by Ustilaginaceae species with potential application as detergents or in cosmetics. This study identified process optimisation potential for CL fermentation based on process modelling and techno-economic analysis. Using a stoichiometric equation based on laboratory data, we calculated the maximum possible CL yield YP/S of 0.45 gCL·gglucose−1 at the biomass yield of 0.10 gBiomass·gglucose−1 with an Ustilago maydis strain. Due to substrate inhibition that may occur at high glucose concentrations, a fed-batch process to increase biomass and CL concentrations was considered in our model. Simulation of different process scenarios showed that the choice of aeration units with high oxygen transfer rates and adaptation of power input to oxygen uptake can significantly decrease electricity consumption. We further assessed scenarios with different fermentation media and CL purification methods, suggesting additional process optimisation potential. Here the omission of vitamins from the fermentation medium proved to be a possible mean to enhance process economy, without compromising CL productivity.